The Relevance Of Ki Hajar Dewantara's Educational Basis "Education That Independent Students" In Differentiation Learning In The Independent Curriculum - Musdahlipah, Musdahlipah; Putri Rahmadani, Dian; Nurhafizh, Hedriansyah; Mohd Rozak, Rezik; Lestari, Helpi; Zullukman, Zullukman (Journal of Basic Education Research, 2024)
Purpose of the study: This research aims to explore the relevance of Ki Hajar Dewantara's basic concept of education, namely "education that liberates students" in the context of differentiated learning in the Independent Curriculum. Ki Hajar Dewantara is known as an Indonesian education figure who encourages an educational approach that respects the uniqueness and potential of each student, and gives them the freedom to develop according to their talents and interests. Methodology: The literature study research method will be used to examine relevant theories, as well as the results of the latest research which examines the relationship between Ki Hajar Dewantara's educational concept and differentiated learning in the context of the Independent Curriculum. Main Findings: A critical analysis of the literature will be conducted to identify similarities, differences, and practical implications of the concepts. Novelty/Originality of this study: The values of freedom, equality and respect for individual uniqueness promoted by Ki Hajar Dewantara are reflected in the differentiated learning practices in the Merdeka Curriculum. Differentiated learning allows for strong inclusion, equity in educational access, and recognition of individual differences in student needs and interests. This concept provides a strong philosophical foundation for creating an inclusive, adaptive, and student-centered learning environment, in accordance with the spirit of freedom, equality, and respect for individual uniqueness.